A Beautiful Bird in the Neighborhood: Canopy Cover and Vegetation Structure Predict Avian Presence in High-Vacancy City - Sebastian Moreno; Andrew J. Mallinak; Charles H. Nilon; Robert A. Pierce (Land)
Urban vacant land can provide important habitat for birds, especially in cities with high concentrations of residential vacancy. Understanding which vegetation features best support urban biodiversity can inform greening strategies that benefit both wildlife and residents. This study addressed two questions: (1) How does bird species composition reflect the potential conservation value of these neighborhoods? (2) Which vegetation structures predict bird abundance across a fine-grained urban landscape? To answer these questions, we conducted avian and vegetation surveys across 100 one-hectare plots in St. Louis, Missouri, USA. These surveys showed that species richness was positively associated with canopy cover (β = 0.32, p = 0.003). Canopy cover was also the strongest predictor of American Robin (Turdus migratorius) and Northern Cardinal (Cardinalis cardinalis) abundance (β = 1.9 for both species). In contrast, impervious surfaces and abandoned buildings were associated with generalist species. European Starling (Sturnus vulgaris) abundance was strongly and positively correlated with NMS Axis 1 (r = 0.878), while Chimney Swift (Chaetura pelagica) abundance was negatively correlated (r = −0.728). These findings underscore the significance of strategic habitat management in promoting urban biodiversity and addressing ecological challenges within urban landscapes. They also emphasize the importance of integrating biodiversity goals into urban planning policies to ensure sustainable and equitable development.